Les mobilités émergentes après la Grande Récession : du vélo partagé à la trottinette électrique. Le cas de la ville de Saragosse (Espagne) - Carlos López-Escolano; Ángel Pueyo Campos (Belgeo)
The effects of the Great Recession and current technological developments influence the attitudes and patterns of mobility in urban and metropolitan areas. They reflect the situation of precarious employment and living conditions, cultural and social changes or the spread of new modes of travel. In this context, two approaches are possible which determine the future of urban mobility: sustainability and smart mobility. They configure an accessible, efficient, attractive and sustainable connectivity model.Focusing on the dual discourse of the legitimization and the conflict of the new mobilities, this article tries to identify some of the new modes of urban mobility that have arisen in the Spanish cities as a consequence of the economic crisis and recent socio-cultural and technological transformations. For this, we will analyze the case of the city of Zaragoza reviewing the changes in mobility, modes of travel and transport policies adopted in recent years.